2020
DOI: 10.1021/acscatal.0c01895
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Transaminase Diversity for the Oxidative Conversion of Natural Amino Acids into 2-Ketoacids and High-Value Chemicals

Abstract: The use of 2-ketoacids is very common in feeds, food additives, and pharmaceuticals, and 2-ketoacids are valuable precursors for a plethora of chemically diverse compounds. Biocatalytic synthesis of 2-ketoacids starting from l-amino acids would be highly desirable because the substrates are readily available from biomass feedstock. Here, we report bioinformatic exploration of a series of aminotransferases (ATs) to achieve the desired conversion. Thermodynamic control was achieved by coupling an l-glutamate oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Compared with regular chemical synthesizing methods (i.e., Eschweiler-Clark reaction, reduction-methylation and hexafluoroacetone protection) [5,6,12], this enzymatic catalyzing route also shows the advantages of a simple process, easily obtainable raw materials and no need of toxic reagents. In addition, with other enzymes for the synthesis of N-methyl-amino acids normally requiring NADPH as the coenzyme, such as transaminase [11] and imine reductase [44], ChlfSOX would serve as a more effective candidate since there is no need of coenzyme regeneration during the catalyzing process.…”
Section: The Application Of Chlfsox For Chiral Resolution Of N-methyl-dl-aspartic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with regular chemical synthesizing methods (i.e., Eschweiler-Clark reaction, reduction-methylation and hexafluoroacetone protection) [5,6,12], this enzymatic catalyzing route also shows the advantages of a simple process, easily obtainable raw materials and no need of toxic reagents. In addition, with other enzymes for the synthesis of N-methyl-amino acids normally requiring NADPH as the coenzyme, such as transaminase [11] and imine reductase [44], ChlfSOX would serve as a more effective candidate since there is no need of coenzyme regeneration during the catalyzing process.…”
Section: The Application Of Chlfsox For Chiral Resolution Of N-methyl-dl-aspartic Acidmentioning
confidence: 99%
“…As an alternative, an enzymatic method has been suggested to be a more environmental-friendly method for the synthesis of N-momomethyl amino acids. Currently, studies have reported several enzymes that are responsible for the synthesis of N-methyl aspartic acid, such as transaminase [11], methylaspartate ammonia lyase [12], aspartate ammonia lyase [13] and aspartase [14]. However, rather than NMDA, it should be noted that these enzymes could only catalyze the synthesis of N-methyl-l-aspartic acid.…”
Section: Introductionmentioning
confidence: 99%
“…The modularity of the aldol reaction catalyzed by pyruvic acid aldolases elongating a broad pool of aldehydes with 2-oxoacids into 4-hydroxy-2-oxoacid products is impressive. The constructed carbon frameworks with this approach are highly valuable due to the manifoldness of the established downstream routes such as 2,4-dihydroxy acids, 2-amino-4-dihydroxy acids, or 3-hydroxy acids [ 12 ]. In the last few years, the attractiveness of aldolase-mediated carbon—carbon bond formation has risen due to the progress in enzyme discoverynd protein engineering efforts.…”
Section: Introductionmentioning
confidence: 99%
“…Biocatalysis has drawn increasing attention as a powerful alternative to traditional, complicated, and dangerous chemical synthesis methods because of its environmental friendliness and safety. , Specifically, an enzyme is a catalyst in the biocatalytic reactions. Microbial-based metabolic engineering, which relies on wild-type or artificial metabolic pathways, has enabled the production of many high-value compounds through intracellular enzyme catalysis. However, the complex in vivo components and reactions make it difficult to monitor the reaction process and isolate the end product . Therefore, in many cases, an in vitro synthetic pathway has been established to accurately monitor each step of the pathway in real time and simplify target compound purification .…”
Section: Introductionmentioning
confidence: 99%